Medicine consumption during breastfeeding and assessment of infant risk - Anne Fayma Lopes Chaves; Alanna Helenn Marques Dias; Ingrid Kerolly Almeida Dias; Juliane Kerly Silva Martins; Rebeca Silveira Rocha; Mônica Oliveira Batista Oriá (Rev Rene)
Objective: to estimate medicine consumption during breastfeeding and the risk to the infant. Methods: descriptive study, carried out in a Primary Health Care Unit with 130 infants. The data collection was donethrough a form with objective questions, analyzed in Epiinfo. Results:73 (56.0%) nursing mothers had used medication during breastfeeding. The most used drugs were antianemics (n=48, 66.0%) and analgesic/antipyretic drugs (n=11, 14.4%). The majority of the drugs consumed were compatible with breastfeeding(n=71, 97.2%), except for Phenobarbital (n=1, 1.4%) and Losartan (n=1, 1.4%. Conclusion: it was evidenced that medicine consumption during breastfeeding was high among nursing mothers, but most of the drugs presented low risk, that is, they were drugs compatible with lactation.